"You're at their mercy": Older peoples' experiences of moving from home to a care home: A grounded theory study. (30th January 2020) - O'Neill, Marie; Ryan, Assumpta; Tracey, Anne; Laird, Liz
Abstract: Background: Internationally, it is recognised that the transition to a care home environment can be an emotional and stressful occasion for older people and their families. There is a paucity of research that takes into consideration the initial phase of the relocation process, incorporating individuals' experiences of the move. Aim: To explore individuals' experiences of moving into a care home. This paper has a specific focus on the preplacement (7 days) and immediate postplacement (within 3 days) period of the move to the care home. Design: A grounded theory method was used to conduct semi‐structured interviews with 23 participants. Results: Data analysis revealed five distinct categories that captured the experience of the preplacement and immediate postplacement period. These were as follows: (a) inevitability of the move: " I had to come here, " (b) making the move: " Abrupt Departures, " (c) decision‐making and exercising choice: " What can I do, I have no choice, " (d) maintaining identity: " Holding on to self " and (e) maintaining connections: " I like my family to be near ." Together, these five categories formed the basis of the concept "You're at their Mercy" which encapsulates the perceived transition experience of the older people within the study. Participants felt that the move was out of their control and that they were "at the mercy" of others who made decisions about their long‐term care. Conclusions: Moving to a care home represents a uniquely significant relocation experience for the individual. Key factors influencing the move were the individuals' perceived lack of autonomy in the pre‐ and postrelocating period of moving to a care home. Nurses have a key role to play in working with older people to influence policy and practice around decision‐making, planning and moving to a care home with greater emphasis on autonomy and choice so that older people do not feel " at the mercy " of others as they navigate such a major transition. Implications for practice: There is a need to standardise approaches and develop person‐centred interventions to support older people considering relocation to a care home and nurses have a key role to play in making this happen.